Containment control of multi-agent systems with input saturation and unknown leader inputs. (August 2021) - Li, Pengyuan; Jabbari, Faryar; Sun, Xi-Ming
Abstract: This paper investigates the containment control problem for multi-agent systems (MASs) with multiple leaders which have non-zero control inputs. Agents' tracking errors are described by a linear system with an external disturbance. The containment control problem is then solved by applying a distributed observer-based output feedback controller. Anti-windup (AW) compensation is designed by convex conditions, to improve the performance in the presence of actuator saturation. Finally, simulations are presented to illustrate the effectiveness of the proposed method.